Estimation of the Optimal Hedge Ratio and Hedging Effectiveness: The Case of The Malaysian Crude Palm Oil Futures Contract - Lee, Bernard Woen Hao (2011)
Operated by Bursa Malaysia and constituting the most liquid Crude Palm Oil (CPO) Futures Contract in the world, there is an eminent concern as to its hedging effectiveness in reducing the risk of the investors’ portfolio in the cash market. Hence, this paper attempts to examine the best minimum variance hedge ratio (MVHR) for the Malaysian CPO Futures Contract using different econometric models. In order to execute the empirical analysis, data from the 16th March 1995 to the 30th June 2011 was drawn and both constant and time-varying MVHRs were estimated using the Ordinary Least Square (OLS), Bivariate Autoregressive(B-VAR), Bivariate Vector Error Correction Model (B-VECM) and both Diagonal Vector(D-VEC) and Baba, Engle, Kroner, and Kraft Multivariate Generalized Autoregressive Heteroscedasticity (BEKK M-GARCH) Models. The hedging effectiveness is evaluated using a risk-return and minimum variance framework - our results indicate that the OLS, BVAR, and B-VECM achieved the highest percentage variance reduction in hedged relative to the unhedged portfolio consistent with findings of Gupta and Singh (2009) and Lien (2009).